The impact of polymorphic variations in the 5p15, 6p12, 6p21 and 15q25 loci on the risk and prognosis of Portuguese patients with non-small cell lung cancer - Mello, Ramon Andrade de (2013)
Polymorphic variants in the 5p15, 6p12, 6p21, and 15q25 loci were demonstrated to potentially contribute to lung cancer carcinogenesis. Therefore, this study was performed to assess the role of those variants in non-small cell lung cancer (NSCLC) risk and prognosis in a Portuguese population. MATERIALS AND METHODS: Blood from patients with NSCLC was prospectively collected. To perform an association study, DNA from these patients and healthy controls were genotyped for a panel of 19 SNPs using a Sequenom® MassARRAY platform. Kaplan-Meier curves were used to assess the overall survival (OS) and progression-free survival (PFS). RESULTS: One hundred and forty-four patients with NSCLC were successfully consecutively genotyped for the 19 SNPs. One SNP was associated with NSCLC risk: rs9295740 G/A. Two SNPs were associated with non-squamous histology: rs3024994 (VEGF intron 2) T/C and rs401681 C/T. Three SNPs were associated with response rate: rs3025035 (VEGF intron 7) C/T, rs833061 (VEGF -460) C/T and rs9295740 G/A. One SNP demonstrated an influence on PFS: rs401681 C/T at 5p15, p?=?0.021. Four SNPs demonstrated an influence on OS: rs2010963 (VEGF +405 G/C), p?=?0.042; rs3025010 (VEGF intron 5 C/T), p?=?0.047; rs401681 C/T at 5p15, p?=?0.046; and rs31489 C/A at 5p15, p?=?0.029. CONCLUSIONS: Our study suggests that SNPs in the 6p12, 6p21, and 5p15 loci may serve as risk, predictive and prognostic NSCLC biomarkers. In the future, SNPs identified in the genomes of patients may improve NSCLC screening strategies and therapeutic management as well.